2015
DOI: 10.3892/etm.2015.2379
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nucleoside analogs on blocking father-to-infant vertical transmission of hepatitis B virus

Abstract: Abstract. The aim of the present study was to observe the efficacy and safety of nucleoside analogs in inhibiting father-to-infant vertical transmission of hepatitis B virus (HBV). Nucleoside analogs compete with HBV DNA polymerase substrate to inhibit DNA polymerase, thus preventing the replication of HBV DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Nucleoside analogs are widely used for the prevention and treatment of several viral infections, including human immunodeficiency virus, hepatitis B virus, and herpes infections ( Albrecht et al, 1970 ; Burchenal et al, 1975 ; Aguirrebengoa et al, 1996 ; Adams et al, 1997 ; Bavoux et al, 2000 ; Quan and Peters, 2004 ; Anderson, 2008 ; Angusti et al, 2008 ; Ambrose et al, 2009 ; Billioud et al, 2011 ; Agarwal et al, 2015 ; Cao et al, 2015 ; Ehteshami et al, 2017 ). Due to their hydrophilic nature, nucleoside analogs depend on a carrier-mediated transport process to permeate through host cell membranes before exhibiting their antiviral activities ( Yao et al, 1996 ; Damaraju et al, 2011 ; Moss et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoside analogs are widely used for the prevention and treatment of several viral infections, including human immunodeficiency virus, hepatitis B virus, and herpes infections ( Albrecht et al, 1970 ; Burchenal et al, 1975 ; Aguirrebengoa et al, 1996 ; Adams et al, 1997 ; Bavoux et al, 2000 ; Quan and Peters, 2004 ; Anderson, 2008 ; Angusti et al, 2008 ; Ambrose et al, 2009 ; Billioud et al, 2011 ; Agarwal et al, 2015 ; Cao et al, 2015 ; Ehteshami et al, 2017 ). Due to their hydrophilic nature, nucleoside analogs depend on a carrier-mediated transport process to permeate through host cell membranes before exhibiting their antiviral activities ( Yao et al, 1996 ; Damaraju et al, 2011 ; Moss et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown similar results; it was safe for fathers with CHB during exposure to ETV pregnancy and the baby had no abnormalities or deformities (24)(25)(26)(27); there was no need to terminate the pregnancy.…”
Section: Discussionmentioning
confidence: 62%